Analisis Vegetasi dan Identifikasi Kandungan Fitokimia Gulma pada Lahan Tebu (Saccharum officinarum L.): Vegetation Analysis and Potentials Phytochemical Identification of Weed in Sugarcane Fields (Saccharum officinarum L.) - Puji Lestari Tarigan; F. Deru Dewanti (Agrocentrum, 2023)
Sugarcane is one of the dry land commodities. Biotic and abiotic factors can influence sugarcane growth. Sugar cane can experience disturbances caused by wild plants around it. Weeds are nuisance plants that can decrease sugarcane production. Besides that, the diversity of weeds also has much potential to become a source of food, industry, and medicine. There are 10 species of weeds were found growing at the same time. Through biological identification, it is known that there are 2 types of weeds broad-leaf weeds and narrow-leaf weeds/grasses. Based on observations, the most dominant weed species is Cayratia trifolia. This weed belongs to the broad-leaf type, has a perennial life cycle, and reproduces by root tubers and seeds. Weeds can be controlled effectively using the 0.5% 240SL method. The most appropriate time for weed control in sugarcane is 60-120 hst. In addition, from the literature review, it is known that all weeds have the potential to be used as medicines for human health and also for biological control. So, this really supports science development for advanced use.